Immunological Reactivity and Intensity of Oxidative Stress in Stable Coronary Artery Disease - GavrilenkoTetiana І.; Lomakovskyi, Oleksandr M.; Pidgaina, Olena A.; Rasputniak, Olga V.; Ryzhkova, Nataliia O.; Grechkovskaya, Natalia V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the relationship between immune response factors and the intensity of oxidation of lipoproteins and proteins in patients with stable coronary artery disease (CAD) to clarify the pathogenesis of coronary atherosclerosis. Materials and methods. A total of 179 patients with stable CAD of II-IV functional class, mean age 56 (49-62) years (main group) and 30 healthy individuals, mean age 49 (45-53) years (control group) were examined. The material for immunological research was peripheral venous blood. To determine the indicators of immunity, flow laser cytometry and enzyme-linked immunosorbent assay were used. Spectrophotometric and fluorometric methods were used to determine the levels of intermediate and final oxidation products of lipids and proteins, as well as antioxidant protection enzymes in the blood serum and in atherogenic lipoproteins. Results. A direct relationship between the activity of lipoprotein peroxidation and protein oxidation with a cell-type immune response and immune inflammation was revealed. Conclusions. The high intensity of lipid peroxidation and protein oxidation in patients with stable CAD (stable angina pectoris) is combined with significant activation of the T-cell component of the immune response (in terms of the ratio of helper and cytotoxic subpopulations of T-lymphocytes, high concentrations of pro-inflammatory cytokines, the state of the CD40/CD40L system, the level of expression of the CD95 apoptosis marker on cells), which indicates interdependence of T-cell immunity and oxidative stress in the pathogenesis of atherosclerosis. The dependence of the hyperproduction of pro-inflammatory cytokines by mononuclear blood cells on free radical oxidation of proteins, peroxidation of apoB proteins and the intensity of antiperoxide protection (catalase and superoxide dismutase enzymes) in patients with stable CAD indicates a contribution to the presence of oxidative stress and the development of immune inflammation. A comprehensive study of the factors of immunological reactivity, the violation of which can lead to the development of immunopathological reactions, and the intensity of oxidation of lipoproteins and proteins in patients with stable CAD helps to clarify the pathogenetic relationship between chronic immune inflammation, endothelial dysfunction and oxidative stress, and also substantiates the expediency of general therapeutic approaches to the treatment of CAD.